A recommendation of breakdown maintenance on vehicle engine camshaft line using reliability centered maintenance and FMEA method - Y. Advin Fajar Nugroho; Uly Amrina; Bonitasari Nurul Alfa (Universitas Mercu Buana, 2020)
A vehicle engine manufacturing company that implements Total Productive Maintenance (TPM) found many breakdowns in the camshaft line from January to May 2019. This study aims to reduce the engine camshaft line breakdown by improving preventive maintenance using the Reliability Centered Maintenance (RCM) method and Failure Mode and Effect Analysis (FMEA). The researchers mapped the breakdown time data per engine and found that the longest breakdown time was on the IGR-0040 engine with 22.23 hours. The current availability ratio of the IGR-0040 machine is 72.88%, and the reliability index is 55%. Furthermore, this research identified machine failure using FMEA and found that six machine components experienced the highest failure rate. The researchers proposed some improvement activities related to the maintenance interval rescheduling period that could increase by 61% reliability